Apoaequorin Differentially Modulates Fear Conditioning in Adult and Aged Rats - (:unkn) unknown (My University, 2016)
Normal aging is associated with a number of changes in behavioral and cellular function, and is often linked to increased susceptibility to cognitive impairment. The hippocampus has been widely implicated in learning and memory, and many forms of learning that are hippocampus-dependent (e.g. trace fear conditioning) are impaired in aged animals. A proposed contributor to aging-related cognitive impairment is aging-related calcium (Ca2+) dysregulation. This dysregulation is thought to result from changes in specific Ca2+-regulatory mechanisms, including abnormal Ca2+ ion channel activity or expression, as well as reduced Ca2+-binding protein (CaBP) expression, which is associated with cognitive and synaptic impairment. Previous data from our lab indicate that a single hippocampal infusion of the CaBP apoaequorin (AQ) is neuroprotective in the event of an ischemic insult, a process characterized by Ca2+-induced excitotoxicity. However, the effect of AQ on fear memory in adult and aged animals has yet to be examined. The current experiments investigate the effect of AQ infusion on trace fear conditioning in adult and aged rats. We firstly demonstrate that a single infusion of AQ 24 h before trace fear acquisition fails to rescue an aging-related trace fear memory deficit. Second, we found that AQ infusion 1 h prior to trace fear acquisition reduces baseline freezing during a cue test in a novel context, suggesting pre-training AQ infusion may mitigate context fear generalization. Furthermore, AQ infusion 1 h prior to trace fear acquisition and 1 h prior to testing results in a reversal of aging-related context fear memory impairment. The results of these studies suggest a possible role for AQ in modifying cognitive function in adult and aged rats.
Keywords: Aging; Calcium-Binding Protein; Fear Conditioning